Legal Protection of Children’s Personal Data in The Digital Age in Indonesia A Comparative of Government Regulation Number 17 of 2025 and General Data Protection Regulation Uni Eropa - Yessi Ainurohwati; Andry Setiawan (Law Research Review Quarterly, 2026)
Advances in digital technology increase the risk of misuse of children’s personal data, thereby placing children as a vulnerable group in the digital space. This study aims to analyze the legal protection of children’s personal data under Government Regulation No. 17 of 2025 and compare it with the European Union’s General Data Protection Regulation. The focus of the study lies on the ability of Government Regulation No. 17 of 2025 to provide protection for children’s personal data. This study employs a normative legal methods using a legislative and comparative law approach. The findings indicate that Government Regulation No. 17 of 2025 has established protections through age limits, parental consent, age verification, supervision, and administrative sanctions. However, these provisions remain focused on administrative compliance and are not yet supported by adequate mechanisms for the restoration of children’s rights, including compensation and data deletion, as well as the absence of an independent supervisory authority. This study recommends strengthening aspects of implementation, institutional framework, and recognition of substantive rights so that the protection of children’s personal data can function optimally.